SOSIALISASI PENGELOLAAN LIMBAH RUMAH TANGGA DALAM MENCEGAH PENCEMARAN LINGKUNGAN DAN GLOBAL WARMING DI SMA NEGERI 1 NARMADA, KABUPATEN LOMBOK BARAT - Susilowati, Lolita Endang; Markum, Markum; Wahyuningsih, Endah; Jaya, Dori Kusuma; Gigentika, Soraya (Universitas Mataram, 2025)
Improper household waste management can cause environmental pollution and contribute to global warming. Therefore, there is a need for community service activities to provide education on household waste management to the students of SMA Negeri 1 Narmada. The goal of this community service activity is to increase the understanding and awareness of SMA Negeri 1 Narmada students regarding the importance of practical steps in household waste management to prevent environmental pollution and mitigate the impacts of global warming. This activity is carried out through outreach using expository methods, participatory methods, and formative evaluation, where students are introduced to the concepts of 3R (reduce, reuse, recycle) and the zero waste movement. The results of the activity show an increase in students' knowledge of the types of household waste and their negative impacts, as well as a better understanding of how to manage waste effectively. This outreach also resulted in positive changes in students' habits, such as separating organic and inorganic waste, using recyclable products, and reducing the use of single-use plastics. The conclusion of this activity is that household waste management outreach has proven effective in raising environmental awareness and can serve as a starting point for creating sustainable behavioral change. It is recommended that similar activities be held regularly and accompanied by collaboration between schools, communities, and the government to strengthen waste management efforts and global warming mitigation in a broader and more integrated manner.